2009
DOI: 10.1007/s10867-009-9162-z
|View full text |Cite
|
Sign up to set email alerts
|

Information processing limits on generating neuroanatomy: global optimization of rat olfactory cortex and amygdala

Abstract: A pattern of widespread connection optimization in the nervous system has become evident: deployment of some neural interconnections attains optimality, sometimes without detectable limits. New results for optimization of layout of connected areas of rat olfactory cortex and of rat amygdala are reported here. One larger question concerns mechanisms-how such minimization is attained. A next question is why a nervous system would optimize rather than just moderately satisfice. A morphogenic proposal that relates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This condition constrains the geometry of the network, provided that energy consumption is efficient. The principle has been thoroughly analysed in the context of the arrangement of the Caenorhabditis elegans NS [111]; the rat olfactory cortex and the amygdala [113]; and the cat sensory and macaque visual cortex [114]. In fact, Cherniak [111] has shown that in C. elegans (or in H. sapiens), rstb.royalsocietypublishing.org Phil.…”
Section: Independent Events In Nervous System Centralization Across Metazoan Phylamentioning
confidence: 99%
“…This condition constrains the geometry of the network, provided that energy consumption is efficient. The principle has been thoroughly analysed in the context of the arrangement of the Caenorhabditis elegans NS [111]; the rat olfactory cortex and the amygdala [113]; and the cat sensory and macaque visual cortex [114]. In fact, Cherniak [111] has shown that in C. elegans (or in H. sapiens), rstb.royalsocietypublishing.org Phil.…”
Section: Independent Events In Nervous System Centralization Across Metazoan Phylamentioning
confidence: 99%
“…If selective pressure does act to maximize the coding efficiency and minimize the cost for the brain, experimental evidence as a consequence of the above selection processes should be expected to be observed (Cherniak and Rodriguez‐Esteban, ). The evidence may include but is not limited to optimizing the ionic channel dynamics and distribution of sodium and potassium channels among axons, optimizing the morphological parameters (e.g., axonal wiring length) of individual neurons within the neuronal dense cortex, and choosing the most economical strategies to represent information by producing trade‐offs between costs and benefits (Laughlin, ; Niven and Laughlin, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the chemical reaction perspective, the coefficients k 0 L and k 1 L are considered as the overall possible reaction rates from |0 A 〉 → |1 A 〉 and |1 A 〉 → |0 A 〉, respectively. Here, in our perspective based on [ 13 19 ], both coefficients are considered to represent the influence of brain’s prefrontal-cortex, which is related to the rational decision, and brain’s amygdala, which is related to the irrational decision, respectively. It is seen in the Eqs.…”
Section: Asano-ohya-khrennikov Quantum-like Modelmentioning
confidence: 99%
“…As mentioned in the Introduction section, we should emphasize that we consider our modification based on the observed amygdala and prefrontal cortex nonlinear interactions [ 13 19 ], as well as the specific functions of both brain’s part [ 9 12 ]. Similar nonlinear interactions can also be found in other physical systems, for instance, in the nonlinear optical systems with two or more different interacting modes (see, e.g., [ 25 27 ]).…”
Section: Modified Asano-ohya-khrennikov Quantum-like Modelmentioning
confidence: 99%
See 1 more Smart Citation